Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

(x-2) + x + (x+2) = 69

3x - 69 -> x - 23

the numbers are 21, 23 and 25.

3x - 69 -> x - 23

the numbers are 21, 23 and 25.

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Let the first odd number be x

second odd number be x+2

third odd number be x+4

the sum of the three consecutive odd integers = 69

Equation:

(x) + (x+2) + (x+4) = 69

3x + 6 = 69

3x = 69 - 6

3x = 63

3x/3 = 63/3

x = 21

The three consecutive odd integers are:

x = 21

x+2 = 23

x + 4 = 25

To check:

21 + 23 + 25 = 69

69 = 69

second odd number be x+2

third odd number be x+4

the sum of the three consecutive odd integers = 69

Equation:

(x) + (x+2) + (x+4) = 69

3x + 6 = 69

3x = 69 - 6

3x = 63

3x/3 = 63/3

x = 21

The three consecutive odd integers are:

x = 21

x+2 = 23

x + 4 = 25

To check:

21 + 23 + 25 = 69

69 = 69